Обман: повесть / Альберт Лиханов ; [художник Г. Новожилов] - Лиханов Альберт Анатольевич (Отрочество, 1981)
Экземпляры: ДБ (1982) / Инвентарный номер: 2138 / Авт.знак: Л 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6